The impact of positive parenting behaviors and maternal depression on the features of young children's home language environments. Issue 2 (19th March 2020) - TREAT, Amy E.; SHEFFIELD MORRIS, Amanda; HAYS-GRUDO, Jennifer; WILLIAMSON, Amy C.
Abstract: This study investigated the associations between maternal depression when infants were 3 to 11 months old ( M = 6 months), and positive parenting behaviors when children were between 12 and 22 months ( M = 17 months) and the home language environment assessed when children were 18 to 28 months old ( M = 23.5 months) in a sample of 29 low-income mother–child dyads. After controlling for maternal education, only teaching behaviors remained a moderate and significant predictor of adult word counts. Observed teaching behaviors significantly predicted conversational turns and marginally predicted child vocalizations; effects sizes were small. Encouraging behaviors were a small and significant predictor of conversational turns and a marginally significant predictor of adult word counts. Maternal depression was a moderate and significant predictor of children's vocal productivity scores and a small, marginal predictor of conversational turns. These findings have important implications for parenting and children's language outcomes.